The Influence of Brand Image, Product Quality and Price on Purchasing Decisions at Starbucks Coffee Multatuli Medan - Elfa Yolanda; Endang Sulistya Rini; Yeni Absah (Proceeding of The International Conference on Business and Economics, 2024)
This research aims to examine the influence of brand image, product quality and price on purchasing decisions at Starbucks Coffee Multatuli Medan. In this research, the researcher distributed 75 questionnaires to consumers of Starbucks Coffee Multatuli Medan using accidental sampling, which is a method for testing coaecudental sampling, whoever the researcher meets by chance can be used as data used for sampling, if he is suitable as a data source and as long as 3 months. The researcher decided on 75 respondents. The analytical model used in this research is a multiple regression model. The results of the t test analysis show that there is a positive and significant influence between brand image, product quality and price on purchasing decisions at Starbucks Coffee Multatuli Medan.